Transfer of Knowledge or Rhetoric of Exile? Bohemian Exiles and their Self-Representation in the Hartlib Papers - Urbánek, Vladimír (Dějiny – teorie – kritika, 2020)
As documented in numerous recent historical studies, migration for religious reasons was closely related to the transfer of knowledge in the early modern period. The aim of this essay is to analyse the self-presentation of migrants from the Bohemian Lands during the Thirty Years’ War who presented themselves as both persecuted religious exiles and as experts or innovators. This mixture of two discourses helped them negotiate their expertise and search for patronage using a correspondence network centred around the London- based polymath Samuel Hartlib. This communication network served as an informal intellectual infrastructure which facilitated knowledge transfer and functioned as an intermediary between the individual interests of historical actors and broader concerns of public interest. The article entails two case studies which discuss correspondence and other manuscript material produced by two historical actors in the 1630s and 1640s. The first deals with a Moravian noble, Johann Christoph Berger of Berg, who presented himself as a technological inventor, mine drainage expert and attempted to meet the demand for useful knowledge. The second case study deals with Cyprian Kinner, a Silesian scholar who reacted to Hartlib’s project of the ‘Office of Address’. Kinner presented himself as an expert in communication and offered to organise a branch of this office in Silesia engaging local scholars with the aim to create a network financed by the English Parliament. Both Berger of Berg and Kinner combined the narrative of exile, using various biblical allusions, with the self-confident rhetoric of experts and innovators who can offer their skills and knowledge in proof of their reciprocal usefulness.